Low noise inverter for poly phase microgrid system - Rahman, Tawfikur; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (The Institute of Electrical and Electronics Engineers, Inc., 2016)
The inverter is a power electronics device which changes DC voltage to AC voltage or vice versa. The synchronous phase inverter is used in the microgrid system to connect the renewable energy sources of minimum phase error. For a high-efficiency power transmission and distribution system, a three-phase inverter is used. The electronic switches of the inverter are controlled by a controller circuit which can be a two-level pulse width modulation (PWM), phase lock loop (PLL) controller, etc. A fixed reference DC voltage and current generators are used for a stable input-output voltage and current to reduce the higher harmonic distortions. An LC lowpass filter has been designed and simulated for the input and output of the system by using MATLAB2014a. The input filter is utilized to reduce the AC ripple component in the DC input supply, and the output filter is used to reduce the higher frequency harmonic distortion from the inverter output supply to maintain the IEEE standard THD < 5%. A balanced microgrid star configuration load and the input DC voltage of ± 250V have been considered in this design. The overall conversion efficiency of the inverter is 97.62% and THD <5%. The results show that the design has better performance and can be used efficiently in the microgrid system.